Analisis Faktor Yang Mempengaruhi Cash Holding Pada Perusahaan Consumer Goods Di Indonesia - Kessya Claudia, Merry Susanti (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The objective of this research was to obtain empirical evidence about the effect of leverage, net working capital, profitability, firm size and board size on cash holding. The subject of this research was consumer goods companies listed in the Indonesia Stock Exchange (IDX) for the period of 2017-2019 with a sample of 31 consumer goods companies. The sample selection technique used was purposive sampling. Data were analyzed using Eviews 10 software. The result of this research showed that net working capital had negative impact toward cash holding, while leverage, profitability, firm size and board size had no impact to cash holding. The implication of this research is that companies and investors need to observe to the company's net working capital because it will affect the company's cash holding.